Človekove pravice in spol v športu - Vodeb, Roman (Šport (Ljubljana), 2018)
In this "confused" times, when people lost their compass, when society think about gender as LGBT and feminist ideology wants, it is necessarily to think philosophically about dilemmas of difference between woman and man in sport. Therefor our approach will be partly psychoanalytical and partly philosophically analytical including morality and fair play. LGBT with their feminist supporters started to call on Article 14 of Constitution of Slovenia and Article 14 of European convention for human rights. They believe that their sexual orientation must not be the reason for discrimination regarding some "human rights" which heterosexuals have. Sport as institution is now confused because it has to face with all this ideology. Therefor it is necessary to help sport in thinking about this now situation.
Keywords: človekove pravice; pravičnost; spol; šport